Integrating psychopharmacology and cognitive remediation to treat cognitive dysfunction in the psychotic disorders. (23rd July 2013) - Medalia, Alice; Opler, Lewis A.; Saperstein, Alice M.
<x content-type="archive" xml:space="preserve">Abstract</x> Cognitive deficits are a prominent and enduring aspect of schizophrenia, which pose a significant barrier to achieving functional goals. The most promising intervention for treating cognitive impairment is cognitive remediation (CR), a behaviorally based therapy associated with medium effect sizes for cognitive and functional outcomes. However, there is a sizeable group of nonresponders whose CR outcomes become limited when the therapeutic approach fails to address individual differences in baseline cognition, motivation variables, and the extent to which CR offers opportunities for generalization. This speaks to a need to develop cognitive interventions that are both personalized and scalable. Emerging data suggest that specific pharmacological agents have the potential to enhance and accelerate behaviorally based CR effects. This article will review the rationale and preliminary evidence to support combining CR and pharmacotherapy. We will review crucial aspects of cognitive interventions that offer the most promise for improving not only cognitive outcomes, but also for enhancing improvement in real-world functioning. Finally, we will address methodological issues to be considered for future research on combined pharmacological and CR interventions.